20, 000 miles : the Cambridge University Indo-African expedition 1960, Cambridge - Colombo - Cape Town /: the Cambridge University Indo-African expedition 1960, Cambridge - Colombo - Cape Town. (2017) - Fenwick, Christopher
No abstract available